2022
DOI: 10.2174/1568026622666220117111858
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of Flavonoids with Various Activities

Abstract: Flavonoids, a series of compounds with C6-C3-C6 structure, mostly originate from plant metabolism. Flavonoids have shown beneficial effects on many aspects of human physiology and health. Recently, many flavonoids with various activities have been discovered, which has led to more and more studies focusing on their physiological and pharmacodynamic activities. The anti-cancer and anti-viral activities especially have attracted the attention of many researchers. Therefore, the discovery and development of flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 153 publications
0
9
0
Order By: Relevance
“…Increasing data suggests that flavonoids may target G-quadruplex structures [ 51 , 52 ]. Luteolin, rutin, quercetin, genistein, kaempferol, hesperidin, myricetin, and daidzein are prevalent dietary flavonoids that have garnered substantial interest for its anti-metastatic, anti-angiogenesis and anti-proliferative activities [ 53 , 54 ]. Previously, one study found that quercetin interacts with monomeric and dimeric G-quadruplex structures generated by a short repetition of the human telomeric region.…”
Section: Interaction Of G-quadruplex Dnas With Dietary Flavonoidsmentioning
confidence: 99%
“…Increasing data suggests that flavonoids may target G-quadruplex structures [ 51 , 52 ]. Luteolin, rutin, quercetin, genistein, kaempferol, hesperidin, myricetin, and daidzein are prevalent dietary flavonoids that have garnered substantial interest for its anti-metastatic, anti-angiogenesis and anti-proliferative activities [ 53 , 54 ]. Previously, one study found that quercetin interacts with monomeric and dimeric G-quadruplex structures generated by a short repetition of the human telomeric region.…”
Section: Interaction Of G-quadruplex Dnas With Dietary Flavonoidsmentioning
confidence: 99%
“…These compounds are responsible for the coloration of leaves, flowers and fruits, and have a fundamental role in the protection of plants as oxidizing and microbial agents [18]. As a class of polyphenols, flavonoids can be divided in flavones (apigenin), flavanones (naringenin), flavans (catechin), flavonoid glycosides, flavonols (quercetin), flavonolignan (silibinin), chalcones (butein), isoflavones (genistein), aurones (aureusidin), leucoanthocynidins (leucopelargonidin) and neoflavonoids (neoflavones) [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are widely distributed in foods and beverages of plant origin, such as fruits, vegetables, tea, and cocoa, in which quercetin is one of the most frequently occurring flavonoids. 12,13 Population-based studies have found that diets rich in quercetin confer lower cardiovascular morbidity. 14,15 In rodent experiments, quercetin has multifactorial pharmacological effects such as anti-inflammatory, immune-regulatory, free radical scavenging, and hypolipidemic effects.…”
Section: Introductionmentioning
confidence: 99%